Bisamide Derivative of Dicarboxylic Acid Contributes to Restoration of Testicular Tissue Function and Influences Spermatogonial Stem Cells in Metabolic Disorders - Pakhomova, Angelina; Pershina, Olga; Nebolsin, Vladimir; Ermakova, Natalia; Krupin, Vyacheslav; Sandrikina, Lubov; Pan, Edgar; Widera, Darius; Dygai, Alexander; Skurikhin, Evgenii (Frontiers in Cell and Developmental Biology, 2020)
Metabolic syndrome can lead to several challenging complications including degeneration of the pancreas and hypogonadism. Recently, we have shown that Bisamide Derivative of Dicarboxylic Acid (BDDA) can contribute to pancreatic restoration in mice with metabolic disorders via its positive effects on lipid and glucose metabolism, and by increasing the numbers of pancreatic stem cells. In the present study, we hypothesized that BDDA might also be effective in restoring hypogonadism caused by metabolic syndrome. Experiments were performed on male C57BL/6 mice with hypogonadism, where metabolic disorders have been introduced by a combination of streptozotocin treatment and high fat diet. Using a combination of histological and biochemical methods along with a flow cytometric analysis of stem and progenitor cell markers, we evaluated the biological effects of BDDA on testicular tissue, germ cells, spermatogonial stem cells in vitro and in vivo, as well as on fertility. We demonstrate that in mice with metabolic disorders, BDDA has positive effects on spermatogenesis and restores fertility. We also show that BDDA exerts its therapeutic effects by reducing inflammation and by modulating spermatogonial stem cells. Thus, our results suggest that BDDA could represent a promising lead compound for the development of novel therapeutics able to stimulate regeneration of the testicular tissue and to restore fertility in hypogonadism resulting from complications of metabolic syndrome.